Determination of Vitamin C Levels in Limes (Citrus aurantifolia Swingle) and Lemon (Citrus limon (L.) Burm. f.) Using the UV Vis Spectrophotometric Method - Gita Rizkasari; Rian Ismail (LPPM STIKes Muhammadiyah Ciamis, 2023)
Vitamin C or ascorbic acid is one of the vitamins needed by the body which functions to help the body's metabolic processes and plays a role in the formation of intercellular collagen. The source of vitamin C in food mostly comes from fresh vegetables and fruit. Limes and lemons are plants that contain vitamin C and have many benefits for the body. This research The aim was to determine the levels of vitamin C in limes (Citrus aurantifolia) and lemon (Citrus Limon) are planted in the area Situmandala Rancah District using UV-Vis Spectrophotometry at a wavelength of 400-600 nm. The samples for this research were limes and lemons. The results of this research showed that the vitamin C level in limes was 0.218% and in lemons it was 0.816%.